A cognitive perspective on the pop it numeracy module: Enhancing Number concepts and working memory through Piaget’s Lens - Mohammad Fauzi, Faiqah; Low , Hui Min; Phoon, Hooi San (Journal of Islamic, Social, Economics and Development, 2025)
Inspired by Piaget's cognitive development theory, the Pop It Numeracy Module introduces an innovative way to improve number concepts and working memory in students with special needs. Education for these learners often lacks strategies suited to their developmental stages, creating significant barriers to building foundational numeracy skills. This study seeks to fill that gap by applying Piagetian principles to a hands-on, interactive learning tool designed for young primary school students with learning disabilities. Using a mixed-methods research approach, the study gathered data through pre-test and post-tests, observations, and teacher interviews to assess the module's impact.The results showed a significant improvement in students' understanding of number concepts and working memory, evidenced by higher test scores and better task performance. Teachers provided positive qualitative feedback, praising the module’s ability to engage students and its alignment with their developmental stages, particularly those in Piaget’s preoperational and concrete operational phases. These findings suggest that the Pop It Numeracy Module not only addresses cognitive development gaps but also promotes active learning and deeper conceptual understanding. The study concludes that Piaget’s cognitive theory provides a strong basis for developing effective numeracy interventions for special needs students. By incorporating tactile, visual, and interactive elements that align with developmental stages, the module shows promise for improving both cognitive and educational outcomes. Further research is encouraged to evaluate its potential for broader application in varied educational settings.